(untitled) (Biological Sciences - PJSIR, 2001)
Organochlorine, organophosphorus and synthetic pyrethroid pesticides, commonly used forcotton crop protection were exam- inedin human blood samplesof pickersandfarmersofcotton growingareasofMultandivision. Atotal of75 samples, collected during 1992and 1993crop seasons were screened forthe presence of thepesticides by analytical procedures involving extrac- tion,cleanupandgaschromatographicdetermination.85%sampleswerefoundtocontainresiduesofstudiedpesticides.However, their quantities were quite low and not harmfull for health except in very few cases.